2022
DOI: 10.1177/01455613221123737
|View full text |Cite
|
Sign up to set email alerts
|

Rapid initiation of nasal saline irrigation to reduce severity in high-risk COVID+ outpatients

Abstract: Objective To determine whether initiating saline nasal irrigation after COVID-19 diagnosis reduces hospitalization and death in high-risk outpatients compared with observational controls, and if irrigant composition impacts severity. Methods Participants 55 and older were enrolled within 24 hours of a + PCR COVID-19 test between September 24 and December 21, 2020. Among 826 screened, 79 participants were enrolled and randomly assigned to add 2.5 mL povidone-iodine 10% or 2.5 mL sodium bicarbonate to 240 mL of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
2
24
0
1
Order By: Relevance
“…As of October 1, 2022, 119 preprints (78.3%) had been published in a scientific, peer-reviewed journal (Figure 2 and eTable 3 in Supplement 1). Two preprints were published in a single journal publication . The median time to publication was 186 days (range, 17-407 days).…”
Section: Resultsmentioning
confidence: 99%
“…As of October 1, 2022, 119 preprints (78.3%) had been published in a scientific, peer-reviewed journal (Figure 2 and eTable 3 in Supplement 1). Two preprints were published in a single journal publication . The median time to publication was 186 days (range, 17-407 days).…”
Section: Resultsmentioning
confidence: 99%
“…According to the characteristics of SARS-CoV-2 replication in the nasal cavity, investigators studied if saline irrigation (gavage) in the nasal cavity would assist in infection recovery. Indeed, a randomized clinical trial using isotonic saline pressured irrigation, supplemented with either sodium bicarbonate or povidone-iodine, significantly reduced hospitalization rate during the early stage of COVID-19 pandemic [36]. Saline, either isotonic or hypertonic, has been used for respiratory conditions as an economical and effective alternative to medications [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Later, Yildiz et al found that nasal saline irrigation with triamcinolone acetonide may relieve COVID-19-related hyposmia (19). Baxter et al found that nasal irrigation with povidone-iodine or sodium bicarbonate helped to reduce disease severity and the duration of hospitalization in patients with COVID-19 (20). These studies seem to prove the efficacy of nasal irrigation to treat COVID-19.…”
Section: Using Nasal Irrigation As An Alternative Therapy For Covid-19mentioning
confidence: 99%